PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN LAVERAGE TERHADAP PROFITABILITAS PERUSAHAAN BANK (STUDI PADA PERUSAHAAN BANK YANG TERDAFTAR DI CGPI TAHUN 2010-2015) - Banasita Pulungga Siwi, 12.05.52.0238; Aini, Nur (Students' Journal of Accounting and Banking, 2016)
This study aimed to examine the effect of good corporate governance mechanisms and leverage on corporate performance Bank. The population in this study is a company listed banks in a survey of The Indonesian Institute for Corporate Governance (IICG) the period of 2010-2015. Sampel in this study are all companies listed banks in GCPI. The method of collecting the data needed to help this research is the method of documentation, namely data collection techniques by using journals-journals, books-books, and view and retrieve data-data obtained from the financial statements submitted Indonesia Stock Exchange that can be downloaded from the website IDX (Indonesia Stock Exchange). The results showed that the mechanism of corporate governance positively affects company performance. While leverage significant negative effect on the performance of the company.Keywords: Corporate Governance, Leverag, Company Performance